Nonoverlapping roles of PD-1 and FoxP3 in maintaining immune tolerance in a novel autoimmune pancreatitis mouse model - Zhang, Baihao; Chikuma, Shunsuke; Hori, Shohei; Fagarasan, Sidonia; Honjo, Tasuku (Proceedings of the National Academy of Sciences - PNAS, 2016)
PD-1 (programmed-death 1), an immune-inhibitory receptor required for immune self-tolerance whose deficiency causes autoimmunity with variable severity and tissue specificity depending on other genetic factors, is expressed on activated T cells, including the transcription factor FoxP3(+) Treg cells known to play critical roles in maintaining immune tolerance. However, whether PD-1 expression by the Treg cells is required for their immune regulatory function, especially in autoimmune settings, is still unclear. We found that mice with partial FoxP3 insufficiency developed early-onset lympho-proliferation and lethal autoimmune pancreatitis only when PD-1 is absent. The autoimmune phenotype was rescued by the transfer of FoxP3-sufficient T cells, regardless of whether they were derived from WT or PD-1-deficient mice, indicating that Treg cells dominantly protect against development of spontaneous autoimmunity without intrinsic expression of PD-1. The absence of PD-1 combined with partial FoxP3 insufficiency, however, led to generation of ex-FoxP3 T cells with proinflammatory properties and expansion of effector/memory T cells that contributed to the autoimmune destruction of target tissues. Altogether, the results suggest that PD-1 and FoxP3 work collaboratively in maintaining immune tolerance mostly through nonoverlapping pathways. Thus, PD-1 is modulating the activation threshold and maintaining the balance between regulatory and effector T cells, whereas FoxP3 is sufficient for dominant regulation through maintaining the integrity of the Treg function. We suggest that genetic or environmental factors that even moderately affect the expression of both PD-1 and FoxP3 can cause life-threatening autoimmune diseases by disrupting the T-cell homeostasis.